Conceptual approaches to update the content of instrumental music teachers pіdgotovki executive - Мозгальова, Наталя (Pedagogy of Higher and Secondary Education, 2014)
Mozgaleva N. G. Conceptual approaches to update the content of instrumental music teachers pіdgotovki executive. The paper proposes a conceptual basis performing instrumental music teacher training. In theory, the essence and specificity of the taxonomic approach in instrumental performance. Defined goals, objectives, principles, training in instrumental teachers. Emphasized that improving the quality of instrumental performance training possible if the transform process of learning to play a musical instrument for organizational and methodical system development which must take into account the identified ideas.